Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fnins.2021.739279
|View full text |Cite
|
Sign up to set email alerts
|

Eyes-Free Tongue Gesture and Tongue Joystick Control of a Five DOF Upper-Limb Exoskeleton for Severely Disabled Individuals

Abstract: Spinal cord injury can leave the affected individual severely disabled with a low level of independence and quality of life. Assistive upper-limb exoskeletons are one of the solutions that can enable an individual with tetraplegia (paralysis in both arms and legs) to perform simple activities of daily living by mobilizing the arm. Providing an efficient user interface that can provide full continuous control of such a device—safely and intuitively—with multiple degrees of freedom (DOFs) still remains a challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Similarly, an individual with tetraplegia managed to pick up objects within just 70s [10]. Tongue has also been used to control upper-limb exoskeletons [57] or wheelchairs [58], [59].…”
Section: A Single-modality Control Interfacesmentioning
confidence: 99%
“…Similarly, an individual with tetraplegia managed to pick up objects within just 70s [10]. Tongue has also been used to control upper-limb exoskeletons [57] or wheelchairs [58], [59].…”
Section: A Single-modality Control Interfacesmentioning
confidence: 99%
“…An upper limb exoskeleton is used, as several studies have successfully demonstrated how it can help restore some of the lost functionality for individuals with movement impairments in the arms [6,7]. Furthermore, the tongue-based interface has previously been shown to be an efficient and suitable interface for individuals with tetraplegia to control an exoskeleton [8,9]. Finally, a semi-autonomous control scheme assists the user in controlling the exoskeleton based on input from a computer vision module, which detects and analyzes nearby objects.…”
Section: Computer Vision Tongue-based Interface Upper Limb Exoskeletonmentioning
confidence: 99%
“…It offers high throughput, both in terms of the number of possible commands and also in terms of how fast they can be issued [16]. Furthermore, several studies have demonstrated that a tongue-based interface can be used by individuals with tetraplegia to control various assistive devices, such as an upper limb exoskeleton [8] or a robotic arm [17]. These considerations have led to the choice of a tongue-based interface.…”
Section: Related Workmentioning
confidence: 99%
“…The intraoral tongue-computer interface (ITCI) introduced in Andreasen Struijk (2006) and enabled full control of a seven-DOF assistive robotic manipulator and a five-DOF ULE by means of tongue movements (Mohammadi et al, 2021b). Usually, an SCI does not affect the tongue motor functionality and its fine movement, which makes the tongue a suitable modality for a control interface (Chu et al, 2018;.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study (Mohammadi et al, 2021b), ten able-bodied individuals controlled the EXOTIC ULE with five DOFs using an adapted version of the commercially available ITCI, iTongue (TKS, Denmark). The interface provided continuous and full control of all five DOFs of the EXOTIC Exo in a single control mode both with and without visual feedback of the interface.…”
Section: Introductionmentioning
confidence: 99%